From budgetary instrument to the budgetary objective: The Portuguese case - Luís Lopes; Margarida Antunes (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
In the contemporary capitalism model and in relation to the functioning of the economy there is a counterproductive view of the state as an institution. This has led to a reversal of the hierarchy between the state and the private sector, since it subordinates states to markets. Fiscal policy has been seen as a channel through which to implement this idea and is no longer associated with the functions that were traditionally assigned to it. Consequently, the state budget as a policy instrument was transformed into the subject of policy objectives, particularly in the Euro Zone with the framing of national fiscal policies. Supiot calls this "governance by numbers" , a form of governance that adopts an "indicators-objective". Portugal has followed the contemporary capitalism model of governance since the 1980s, although Portuguese fiscal policy in the beginning also reflected the development of the welfare state. In the 1990s, the Portuguese government assumed "governance by numbers" and since joining the Euro Zone practically the only objective of Portugal's fiscal policy has been compliance with their "indicators-objective". This article aims to analyse the reconfiguration of Portuguese fiscal policy as a result of the "governance by numbers" of the Euro Zone. In the final section, we will also present some considerations regarding points that must be taken into account in debates on the European budgetary rules.
Keywords: E62; E65; H5; 330; Portuguese fiscal policy; Policy-making; Contemporary capitalism model; Euro Zone; Budgetary rules